Hepatitis B and C virus infection and diabetes mellitus: A cohort study - Hong, Y.S.; Chang, Y.; Ryu, S.; Cainzos-Achirica, M.; Kwon, M.J.; Zhang, Y.; Choi, Y.; Ahn, J.; Rampal, S.; Zhao, D.; Pastor-Barriuso, R.; Lazo, M.; et al. (Nature Publishing Group, 2017)
The role of hepatitis virus infection in glucose homeostasis is uncertain. We examined the associations between hepatitis B virus (HBV) or hepatitis C virus (HCV) infection and the development of diabetes in a cohort (N = 439,708) of asymptomatic participants in health screening examinations. In cross-sectional analyses, the multivariable-adjusted odds ratio for prevalent diabetes comparing hepatitis B surface antigen (HBsAg) (+) to HBsAg (−) participants was 1.17 (95% CI 1.06–1.31; P = 0.003). The corresponding odds ratio comparing hepatitis C antibodies (HCV Ab) (+) to HCV Ab (−) participants was 1.43 (95% CI 1.01–2.02, P = 0.043). In prospective analyses, the multivariable-adjusted hazard ratio for incident diabetes comparing HBsAg (+) to HbsAg (−) participants was 1.23 (95% CI 1.08–1.41; P = 0.007). The number of incident cases of diabetes among HCV Ab (+) participants (10 cases) was too small to reliably estimate the prospective association between HCV infection and diabetes. In this large population at low risk of diabetes, HBV and HCV infections were associated with diabetes prevalence and HBV infection with the risk of incident diabetes. Our studies add evidence suggesting that diabetes is an additional metabolic complication of HBV and HCV infection.